Mewujudkan Desa Wisata melalui Pembekalan Clean, Health, Safety & Environment, Pelayanan Prima dan Exploring, Packaging & Presentation - Sintia Safrianti; Risnita Tri Utami; Dedi Pardiansyah; Yulfiperius Yulfiperius (Universitas Prof. Dr. Hazairin, SH, 2021)
Realizing a Tourism Village through Provision of Clean, Health, Safety & Environment, Excellent Service and Exploring, Packaging & Presentation Sumber Urip Village, Selupu Rejang District, Rejang Lebong Regency is one of the tourist villages in Bengkulu Province that requires tourism development. The Ministry of Tourism and Creative Economy of the Republic of Indonesia in collaboration with Universitas Prof. Dr. Hazairin, SH Bengkulu held the development of Regional Tourism Village 1 A (Sumatra) with the aim of providing understanding to participants about the importance of implementing clean, health, safety & environment, excellent service and explore, packaging & presentation in building a tourist village. Another goal was to increase the tourism awareness movement so that it could develop the cultural and tourism potential that exists in tourist villages. The activity was carried out on September 8, 2020 and continued with assistance in Sumber Urip Village. The technical guidance was attended by 25 participants from tourism-aware community groups, village-owned enterprises, village officials and assistants from students. Overall, the activity was successful and received a positive response from the participants. 100% of participants expressed satisfaction with the material about the development of tourist villages presented in this community service activity.